Safeguarding Women’s Constitutional Rights in the Judicial Reviews of Marriage Law on the Minimum Married Age Limit - Hamidin, Hamidin; Alfitri, Alfitri (Mazahib, 2021)
The Constitutional Court seems inconsistent when examining the same legal issue, i.e., the constitutionality of the minimum married age limit for women, but with different decisions. In the 2014 decision, the Court rejected the petition, while in the 2017 decision, the Court accepted it. This paper analyzes the considerations of constitutional judges in deciding the case to understand whether women’s constitutional rights have been protected in both decisions. Using the case and statutory approach, this article concludes that the 2014 decision rejecting the petition to increase the minimum married age limit for women does not fulfill women’s constitutional rights. Sixteen years old as the minimum age limit for women and nineteen years for men is discriminatory and deprives girls’ rights to health and education. The judges’ consideration in the 2017 decision, which granted the petition, was that determining the minimum married age limit is a legal policy. Still, if the policy contradicts the 1945 Constitution, citizens can challenge its constitutionality. The Marriage Law is a past product, so it needs to be adapted to developments and the 1945 Constitution’s norms. The difference in the Constitutional Court’s decisions on examining the same issue is due to different interpretations and efforts to protect the constitutional rights of citizens.